Young boy having Enteric Fever passed through ICU due to Acute respiratory distress syndrome luckily survived - Islam, Quazi Tarikul; Salim, Mohammad; Tasnim, Refaya; Mihi, Tangila Jahan (Bangladesh Journal of Medicine, 2022)
Being part of a developing world, most of our population suffers from various infectious diseases, enteric fever is one of the commonest of all. A greater percentage of affected children and young adults recover without any complications. As its initial symptoms are very benign, sometimes proper treatment is delayed and that can lead to morbid situation. Our presented case is important to get reported because here a young man was about to die due to one of the rarest respiratory complications of enteric fever that very rapidly led to MODS. Fortunately, he survived for all the prompt clinical judgements were taken in time. Bangladesh J Medicine 2022; 33: 304-307